EN 1785:2003 method for the identification of ionizing treatment in poultry meat products: optimization of the accelerated solvent extraction procedure - Maria Campaniello; Rosalia Zianni; Andrea Chiappinelli; Annalisa Mentana; Valeria Nardelli (Italian Journal of Food Safety, 2025)
X-ray irradiation is a non-thermal technology used for food preservation and sanitization to prolong shelf life. To evaluate the fraudulent use of X-ray treatment, in this study, an accelerated solvent extraction method was optimized for the extraction of lipids and 2-dodecylcyclobutanone (2-DCB), reducing analysis time and solvent consumption compared to Soxhlet extraction reported in the standard EN 1785:2003 method. The qualitative confirmation method was tested on different processed poultry meats, i.e., sausages and hamburgers, irradiated at different dose levels, that is, 0.5, 1.0, and 3.0 kGy. The analytical parameters investigated, namely method linearity, selectivity, minimum dose level, diagnostic sensitivity and specificity, and recovery, showed that the proposed method is suitable for routine analysis in official controls to determine 2-DCB as an irradiation marker.